Prototype of a candy sorting machine - Hazizan, Hairul Ikhwan; Rusli, Ahmad Najmie (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project presents a prototype of a candy sorting machine designed to streamline the sorting process based on color detection. As the demand for efficient candy production increases, manual sorting becomes time-consuming and prone to errors. The proposed machine addresses this issue by automatically identifying and sorting candies according to their colors in a systematic and organized manner. The main objective is to achieve accurate color detection, uniform distribution, and efficient sorting using Arduino-based control. The system's design incorporates an Arduino microcontroller, color sensors, and motors to drive the sorting mechanism. The development also includes custom Arduino code to handle color detection and implement the sorting logic. This prototype provides a cost effective and scalable solution to enhance productivity in small- to medium-scale candy manufacturing environments.